Civil-Military Discordance and the Perpetuation of Khaki Capital Post-2021 Coup in Myanmar - Simanullang, Ribka Priskila; Kartini, Evida (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2025)
The February 2021 coup d’état in Myanmar, led by Min Aung Hlaing, abruptly ended the country’s brief period of democratization. The coup has sparked the Civil Disobedience Movement (CDM), marking the largest civil resistance movement in Myanmar’s history. Using Schiff’s (2008) concordance theory, this study analyzes how Myanmar’s persistent failure to achieve civil-military concordance has fostered fundamentally asymmetrical civil-military relations, ultimately facilitating the reemergence of military rule in 2021. Critics of the coup highlighted the rooted influence of khaki capital, a long-standing strategy through which the military generates and monopolizes economic opportunities, thereby reinforcing its hegemony following the coup. Additionally, the evolution in the military’s economic participation, ranging from institutional privileges to individualized benefits, has further solidified its economic dominance. Utilizing a qualitative approach grounded on extensive literature reviews, this study explores the complex interplay between Myanmar’s political discordance and the military’s deeply rooted economic interests. These interconnected factors sustain a vicious cycle of military authoritarianism and khaki capital, demonstrating remarkable resilience to change.